Physiological responses of Eucalyptus x urograndis to glyphosate are dependent on the genotype - De Carvalho, Leonardo Bianco [UNESP]; Duke, Stephen Oscar; Da Costa Aguiar Alves, Pedro Luis [UNESP] (Instituto de Pesquisa e Estudos Florestais (IPEF), 2018)
Experiments were conducted in a growth chamber aiming to evaluate glyphosate impacts on gas exchange of two Eucalyptus x urograndis genotypes and to verify whether alterations in some metabolic and anatomical characteristics could be related to different plant responses. In a first experiment, treatments consisted of six doses of glyphosate (range from 18 up to 720 g ae ha-1) and two eucalyptus genotypes (C219 and GG100), plus a herbicide-free control for each genotype. CO2 assimilation rate, transpiration rate, stomatal conductance (1, 2, 4, and 7 days after treatment - DAT), leaf thickness and stomatal index (30 DAT) were evaluated. In a second experiment; treatments consisted of applying glyphosate at 180 g ae ha-1 to the same genotypes, also maintaining a herbicide-free control for each genotype. We evaluated leaf contents of glyphosate, amino-methyl-phosphonic acid (AMPA), and shikimic acid at 1, 2, 4, and 7 DAT. As glyphosate dose increased (18 up to 720 g ae ha-1), CO2 assimilation rate, transpiration rate, and stomatal conductance decreased fastest and strongest in the GG100 (31%) compared to the C219 genotype (22%). Shikimic acid accumulated in both genotypes, with the highest levels in the GG100 genotype (5 times greater), at 1 and 2 days after spraying glyphosate at a single dose of 180 g ae ha-1. No significant differences occurred between genotypes in glyphosate content, leaf thickness, and stomatal index. AMPA was not detected in either genotype. Gas exchange alteration due to glyphosate exposure is dependent on eucalyptus genotype, and it may be in part explained by a differential accumulation of shikimic acid, but it probably does not relate to leaf thickness, number of stomata, and glyphosate absorption or degradation.
Keywords: Eucalyptus; Gas exchange; N-(phosphonomethyl)glycine; Shikimic acid